Global Governance and the Role of Intergovernmental Organisations in Promoting Global Peace and Security - Aluede, Jackson A.; Agbawn, Matthew Onalo (ABUAD Journal of Social and Management Sciences, 2023)
This paper examines the role of intergovernmental organisations (IGOs) in promoting international peace and security in different parts of the world. The paper reveals that the post-World War II international system ushered in a new era that witnessed not only the proliferation of IGOs driven by the desire to promote peace and security in their respective regions, but also, engaged in peacekeeping missions in restoring stability in conflict zones. The paper affirms that the provision of Chapter VIII of the United Nations (UN) Charter is instrumental in the increase in the number of IGOs across different regions of the world. The paper establishes that one of the fundamental achievements arising from the establishment of IGOs is that it has enabled the respective regions of the world to respond to the outbreak of violent conflicts through peacekeeping and other conflict resolution mechanisms. The paper examines the role of IGOs in promoting international peace and security through the lenses of global governance. Global governance is both a phenomenon and theory that provides explanations on the factors that influenced the nature, pattern, and processes of international organisations, especially IGOs since the post-Cold War period. The paper admonishes world leaders to embrace the propositions of global governance, as it would enable them to achieve their objectives. It utilises both primary and secondary sources to analyse and interpret the subject matter.